Implementasi ERP Odoo Modul Point of Sale untuk Meningkatkan Operasional Ritel di Toko Ezie - Irmayanti, Ade; Wulandari, Niken; Soraya, Ayu (Fakultas Teknik Universitas Persada Indonesia YAI, 2024)
Toko Ezie, a retail business in Nanga Bulik, Lamandau Regency, Central Kalimantan, specializesin selling furniture, household appliances, and bedroom accessories. Established in 2010, TokoEzie still manages its operations manually, particularly in sales recording, inventory management,and financial tracking. This manual system causes problems such as data inconsistency, recordingerrors, and operational inefficiencies. This research aims to analyze the requirements and benefitsof implementing an Enterprise Resource Planning (ERP) system, specifically the Point of Sale(POS) module, to improve Toko Ezie's operational efficiency and effectiveness. This study uses aqualitative descriptive approach with a case study method. Data were collected throughinterviews, observations, and documentation from the owner and staff of Toko Ezie. The researchfindings indicate that the implementation of an Odoo-based ERP system in the POS module willautomate sales processes, monitor stock in real-time, and streamline financial recording. Theintegration between the POS, inventory, and financial modules is expected to minimize manualerrors, improve data accuracy, and optimize customer service. This ERP implementation isanticipated to provide a long-term solution for enhancing the business performance of Toko Ezie.